Analysis of Main Morphometry Characteristic of Watershed and It’s Effect to The Hydrograph Parameters - I Gede Tunas; Nadjadji Anwar; Umboro Lasminto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2017)
Until today, the development of synthetic unit hydrograph model is still based on morphometry characteristic of watershed or combine with other parameters. According to Sri Harto (1985), There are at least four main characteristic morphometry of watershed which highly influenced to the hydrograph and can be easily quantified namely watershed area (A), main river length (L), main river slope (S) and form factor (FB). This research aim is to analyze and verify these four factors and it’s effect to the three of hydrograph parameters i.e. peak time (TP), peak flow (QP) and base time (TB). This research was carried out in eight watersheds in Central Sulawesi Province  Indonesia as the base of variable preparation to develop synthetic unit hydrograph model. Main morphometry analysis of watershed was conducted by using geographical information system (GIS) software, referring to Indonesia Topographic Map (RBI) data combined with Digital Elevation Model-Shuttle Radar Topographic Mission (DEM-SRTM) data, to determine the area (A), main river length (L), main river slope (S) and form factor (FB) of every analyzed watershed. The research showed that eight observed watersheds had an area (A) of 23.88 km2 to 144.73 km2, main river length (L) of 10.31 km to 28.69 km, main river slope (S) of 0.03422 to 0.10812 and form factor (FB) of 0.21 to 0.49. From correlation analysis, It seen that the watershed area affected very well to peak flow (QP) with correlation coefficient of 0.98. The main river length also affected very well to the peak time (TP) with correlation coefficient of 0.99. Two others morphometry parameters namely main river slope (S) and form factor (FB) did not show the effect which could be concluded. These two parameters showed low correlation coefficient.